The role of geography in the analysis of industrial development strategies within the spatial organisation of a region - Wali Ayad Ayid (Bulletin of Geography. Socio-Economic Series, 2014)
Through presenting the main axes in this study, it is clear that identifying a precise concept of industrial development is related to a wider idea of development. Despite that, the geographical view gives a wider and more comprehensive concept of the industrial development. Moreover, balanced spatial development is closely related to industrial and agricultural development within the space of a geographical region. Industry and agriculture represent productive activities which form the economic basis for a region. Industrial development is the most important tool which is used in developing rural areas. Moreover, industrial development has a great role in developing other activities, especially services in a region. This is done through the capability of industry to provide requirements of other activities and absorb labour force surplus from other economic sectors. In addition, the industry sector increases economic revenues for the region and raises the individuals’ incomes.